2019
DOI: 10.1021/acs.est.9b02701
|View full text |Cite
|
Sign up to set email alerts
|

Improved Inversion of Monthly Ammonia Emissions in China Based on the Chinese Ammonia Monitoring Network and Ensemble Kalman Filter

Abstract: Ammonia (NH3) emission inventories are an essential input in chemical transport models and are helpful for policy-makers to refine mitigation strategies. However, current estimates of Chinese NH3 emissions still have large uncertainties. In this study, an improved inversion estimation of NH3 emissions in China has been made using an ensemble Kalman filter and the Nested Air Quality Prediction Modeling System. By first assimilating the surface NH3 observations from the Ammonia Monitoring Network in China at a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
56
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(80 citation statements)
references
References 66 publications
10
56
1
2
Order By: Relevance
“…An inverse study found that the MEIC inventory underestimated NH3 emissions by 30% nationally and by > 40% in eastern and central regions using observations over the same time period as our study (Kong et al, 2019). HiNH3 increases the anthropogenic emissions of NH3 in MEIC by 50%.…”
Section: Sensitivity Simulationssupporting
confidence: 56%
See 2 more Smart Citations
“…An inverse study found that the MEIC inventory underestimated NH3 emissions by 30% nationally and by > 40% in eastern and central regions using observations over the same time period as our study (Kong et al, 2019). HiNH3 increases the anthropogenic emissions of NH3 in MEIC by 50%.…”
Section: Sensitivity Simulationssupporting
confidence: 56%
“…SO2, HCHO, and NH3 emissions may influence the modeled HMS. Recent studies have shown, although SO2 emissions are well understood, that there may be large uncertainties in emissions of NH3 and HCHO in China (Pan et al, 2018;Kong et al, 2019;Liu et al, 2019;Song et al, 2019a).…”
Section: Sensitivity Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, depending on the aerosol pH and pollutant compositions, the major multiphase oxidation pathways may change from reactions of NO 2 and O 3 at pH greater than 4.5 to O 2 (catalyzed by transition metal ion, TMI) and H 2 O 2 at pH less than 4.5 (Cheng et al, 2016). Unlike the negative feedback between aerosol loadings and their photochemical production (Makar et al, 2015;Kong et al, 2015), the multiphase reactions induce a positive feedback mechanism, i.e., higher particle matter levels lead to more aerosol water, which accelerates sulfate production and further increases the aerosol concentration (G. J. Zheng et al, 2020;Su et al, 2020;Cheng et al, 2016).…”
mentioning
confidence: 99%
“…3, respectively). In the CTRL scenario, emissfNH3 has been set to 2, as recent studies using top-down inverse modeling (Van Damme et al, 2018;Wang et al, 2018;Zhang et al, 2018a;Kong et al, 2019) and direct measurement found that previous bottom-up inventories might underestimate the NH3 emissions, and MEIC inventory was estimated to under-predict NH3 emissions by about 40% over the 10 North China Plain (Kong et al, 2019). As shown in Table S7 of Supplement, doubling the NH3 emissions better match the observed ammonia and ammonium at urban Beijing sites during wintertime (Meng et al, 2011;Liu et al, 2017;Song et al, 2018).…”
Section: Wrf-chem Model Configuration and Scenariosmentioning
confidence: 99%